Genetic polymorphisms in cGAS-STING-mediated type I interferon innate immune signaling pathway are associated with DLBCL - Zhou, Qirui; Jia, Ruinan; Chen, Jinlin; Tan, Yang; Ma, Yuechan; Luan, Mengfan; Sheng, Xue; Han, Xiao; Li, Shuying; Lu, Fei; Ji, Chunyan; Wang, Dongmei; et al. (Frontiers in Immunology, 2025)
BackgroundDiffuse large B cell lymphoma (DLBCL) is a highly heterogeneous lymphoid neoplasm characterized by diverse gene expression profiles and genetic alterations, resulting in substantial variations in clinical features and response to therapy. The cyclic GMP-AMP synthase (cGAS)-stimulator of interferon genes (STING) pathway plays a central role in innate immune response and affects the development of DLBCL. However, the relationship between genetic polymorphisms in genes involved in the cGAS-STING-mediated signaling pathway and their role in DLBCL remains underexplored.MethodsA total of 147 patients with DLBCL and 247 healthy controls were recruited. Single nucleotide polymorphism (SNP) genotyping was conducted using the MassARRAY platform. We evaluated the associations between the selected SNPs and DLBCL susceptibility, clinical features, and survival.ResultsIn our study, TREX1 rs11797 and CXCL10 rs4508917 showed significant association with DLBCL susceptibility. IFNB1 rs1051922 was correlated with white blood cell (WBC) and monocyte count at diagnosis. TREX1 rs11797 and IFNB1 rs1051922 were associated with chemotherapy response in DLBCL. Moreover, PRMT1 rs975484 and CXCL10 rs8878 were associated with the overall survival of patients with DLBCL. Notably, PRMT1 rs975484 was also correlated with hemoglobin (HGB) level, and may serve as an independent favorable prognostic factor in DLBCL.ConclusionsOur findings suggest that SNPs involved in cGAS-STING-mediated type I interferon pathway may influence DLBCL susceptibility, treatment response, and prognosis, highlighting their potential as biomarkers for risk stratification and for guiding individualized disease monitoring.